Classification of Quasi-Sum Production Functions with Allen Determinants - Aydin, Muhittin Evren; Mihai, Adela (Univ Nis, Fac Sci Math, 2015)
In this paper, we derive an explicit formula for the determinant of Allen's matrix of quasi-sum production functions. We completely classify the quasi-sum production functions by using their Allen determinants. Further, we give some geometric applications of Allen determinants.
Keywords: Production function; quasi-sum production function; Allen elasticity of substitution; production hypersurface